2018
DOI: 10.1136/archdischild-2017-313756
|View full text |Cite
|
Sign up to set email alerts
|

Two-year neurodevelopmental outcomes of extremely preterm infants treated with early hydrocortisone: treatment effect according to gestational age at birth

Abstract: In an exploratory analysis of neurodevelopmental outcomes from the PREMILOC trial, early low-dose hydrocortisone was associated with a statistically significant improvement in neurodevelopmental outcomes in infants born at 24 and 25 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 20 publications
(14 reference statements)
2
48
0
Order By: Relevance
“…These findings are in accordance with those of previous reports, showing that selective neonatal hydrocortisone treatment using higher doses (starting dose of 5 mg/kg/day tapered over a minimum of 3 weeks) had no detectable long-term effects on either neurostructural brain development at TEA, brain growth or neurocognitive outcomes at preschool age 17–20. They are also consistent with 2-year clinical outcomes of the population recruited in the trial, demonstrating that early low-dose hydrocortisone treatment was not associated with a statistically significant difference in neurodevelopment at 2 years of age 8 9. While waiting for preschool-age clinical assessment, the present data add further reassuring evidence supporting the neurodevelopmental safety of hydrocortisone use in extremely preterm infants, in particular in terms of the vulnerability of WM to postnatal steroids 21…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in accordance with those of previous reports, showing that selective neonatal hydrocortisone treatment using higher doses (starting dose of 5 mg/kg/day tapered over a minimum of 3 weeks) had no detectable long-term effects on either neurostructural brain development at TEA, brain growth or neurocognitive outcomes at preschool age 17–20. They are also consistent with 2-year clinical outcomes of the population recruited in the trial, demonstrating that early low-dose hydrocortisone treatment was not associated with a statistically significant difference in neurodevelopment at 2 years of age 8 9. While waiting for preschool-age clinical assessment, the present data add further reassuring evidence supporting the neurodevelopmental safety of hydrocortisone use in extremely preterm infants, in particular in terms of the vulnerability of WM to postnatal steroids 21…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the PREMILOC clinical trial tested early low-dose hydrocortisone as an alternative treatment, with potentially fewer neurodevelopmental consequences, in infants born extremely preterm at high risk of BPD. This trial showed a significant improvement in the rate of BPD-free survival at 36 weeks postmenstrual age (PMA),7 without detectable adverse neurodevelopmental outcomes at 2 years of age in hydrocortisone-treated infants 8 9. Although definitive proof of the neurodevelopmental safety of hydrocortisone requires further long-term assessment, early prediction of neurodevelopmental outcomes of very immature infants is still a critical point in prognostic discussions with families of infants born very preterm.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,17 Our analysis confirms an association between early lowdose hydrocortisone exposure and late-onset sepsis; nonetheless, treatment was associated with a significantly improved survival without BPD at 36 weeks PMA and survival to discharge, with no adverse effects on neurodevelopmental outcomes at 2 years. [16][17][18][19] Follow-up of a small number of children (n = 27) at age 5-7 years suggested a correlation between early hydrocortisone treatment and later neurocognitive impairment 34 ; however, the 2-year outcomes of 694 children enrolled in all these studies showed no adverse neurodevelopmental effects and identified possible benefits. Longer-term follow-up of previous cohort studies also have been reassuring.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15] These trials extended hydrocortisone therapy beyond the first postnatal week and used a dose of 1-2 mg/kg/day, which has been shown to moderately but significantly increase serum cortisol concentrations in extremely preterm neonates compared with placebo. 12 Although 2-year follow-up data have been consistently reassuring, 7,[16][17][18][19] the effect of early hydrocortisone treatment on survival without BPD and potential side effects remain unclear. Therefore, we undertook an individual patient data metaanalysis of clinical trials to examine the effect of prophylaxis of early adrenal insufficiency on these outcomes.…”
mentioning
confidence: 99%
“…There is anecdotal evidence that starting doses of dexamethasone as low as 0.05 mg/kg/day might be effective [136, 137] but the Minidex RCT failed to recruit enough participants to confirm this. Low-dose prophylactic hydrocortisone also reduced BPD [138] with improved neurological outcomes in a subgroup of infants of less than 25 weeks’ gestation [139]. …”
Section: Strategiesmentioning
confidence: 99%